Evaluating the Impact of Nigeria’s Fuel Subsidy Regime - Beedell, Estan (Université d'Ottawa | University of Ottawa, 2017)
Nigeria, since early in its history as an independent country, has been one of Africa’s main oil exporters. As oil came to dominate its economy, the Nigerian government adopted interventionist policies in the sector. Price ceilings on refined petroleum products have been supported by a complex subsidy regime combining partial nationalization of the upstream and downstream oil sectors with subsidy payments to private suppliers. The increasing fiscal burden of the subsidies, combined with international pressure to eliminate fossil fuel subsidies in light of evidence of the destructive effect of greenhouse gases, has pushed the Nigerian government to attempt to reform the subsidy regime several times. However, popular and political resistance has prevented the complete removal of price ceilings and subsidies. This paper looks into the major arguments in favour of subsidies, and tests their validity by evaluating the economic, social and political impacts of Nigeria’s subsidy regime. Analysis is based on a literature review supported by data collected by the Nigerian National Bureau of Statistics and other organizations. Findings suggest the subsidy regime has created economic inefficiency, exacerbated negative externalities associated with fossil fuels, and worsened macroeconomic stability through procyclical government spending. It has not achieved its desired social benefits, as the subsidies are regressive, and has not improved access to energy, as subsidies divert investment from public power infrastructure. Lastly, the interplay between subsidies, rent-seeking, and patronage has likely worsened Nigeria’s quality of governance. Nonetheless, the subsidy regime enjoys widespread popularity as a tangible means by which natural resource wealth is redistributed.